Developing and validating an instrument for measuring m-commerce adoption: an exploratory analysis - Sadi, Saifullah; Noordin, Mohamad Fauzan (INTI International University, 2011)
Mobile Commerce, also known as, M-commerce is thought to be the next big phase in this technologically dependent society after E-commerce era. However, its adoption and level of use is low in Malaysia compared to others nations such as Korea, Singapore, and Japan. This study aims to identify some factors that affect the adoption of M-commerce in Malaysia based on traditional technology models such as Theory of Reason Action (TRA), Theory of Planned Behavior (TPB), Technology Acceptance Model (TAM) and Diffusion Innovation theory (DOI). In this research, an exploratory factor analysis was conducted on different measures to identify the underlying factors influencing the adoption of M-commerce. The findings revealed that all the thirteen (13) factors were statistically significant and can affect the adoption of m-commerce.